Israel : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2007)
This 2006 Article IV Consultation highlights that strong macroeconomic conditions and sound domestic policies have significantly improved Israel's growth performance and prospects, notwithstanding political uncertainties and the hostilities in the north during the summer of 2006. Inflation pressures are subdued, and monetary policy has been easing as of late. Financial soundness indicators have been recovering although some weaknesses on bank balance sheets that relate mainly to previous boom-bust cycles remain. For 2007, real GDP growth is forecast about 4 1\2 percent.